Sexuality and self-concept of morbidly obese women who are sexually attracted to men after bariatric surgery: a phenomenological study - José Granero-Molina; María del Mar Jiménez-Lasserrotte; Cristina Arias Hoyos; María José Torrente Sánchez; Cayetano Fernández-Sola; María Dolores Ruiz-Fernández (BMC, 2024)
Abstract Background Morbid Obesity (MO) is a public health problem that affects a person's physical, psychological and sexual well-being. Women with MO are affected by their body image and self-concept, and obesity stigma may affect women in social and sexual relationships. Objective To describe and understand the experiences of morbidly obese heterosexual women (who are sexually attracted to men) in relation to their body image and sexuality after bariatric surgery. Methodology Qualitative study using Merleau-Ponty's hermeneutic phenomenology as a philosophical framework. Data collection took place between 2020 and 2021 in a southern Spanish province. A total of 22 in-depth interviews were conducted using open-ended questions until data saturation was reached. Results Two main themes were identified: (1) "Escaping from a cruel environment": weight loss to increase self-esteem; with the sub-themes: 'I love myself now', and 'Body image and social relationships; a vicious circle; (2) "Now, I am truly me": accepting my body to reclaim my sexuality, with the sub-themes: 'The body as the focal point of sexuality', and 'When regaining your sex drive reignites your sex life and relationship'. Conclusion Weight loss and body acceptance radically change morbidly obese women's sex lives after bariatric surgery. They rediscover their bodies, have increased self-esteem, and see improvements in their social relationships and sexuality. These women feel seen, loved and desired, and now value their body image and femininity. As they go through continuous improvements following bariatric surgery, they gradually regain self-esteem, acceptance of their bodies and control over their sex life. Even though the women's partners benefit from these improvements, they seem to be afraid of being left.